2018
DOI: 10.1111/bjso.12287
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐national analysis of sex differences in prisoner's dilemma games

Abstract: In a comprehensive cross‐national study involving samples from 12 different countries that were representative for the adult populations in terms of age and sex (N = 2,429), we found that women cooperate significantly less overall than men in fully incentivized one‐shot prisoner's dilemma games. This gender gap in cooperation can be explained by the fact that women hold lower expectations regarding the cooperativeness of their anonymous interaction partners. These results contradict both the common stereotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…This sampling bias substantially limits extrapolation of these findings to different geographic regions [ 16 ]. The recent work by Dorrough and Glöckner [ 17 ], measuring cooperativeness in continuous Prisoner’s Dilemma games across 12 different countries worldwide, has demonstrated that, although men generally tended to be more cooperative than women, results differed considerably between countries. Another important step which may bring us closer to understanding the mechanisms underlying same-sex cooperative behavior would be extension of the research area towards societies with different traditional socio-economic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sampling bias substantially limits extrapolation of these findings to different geographic regions [ 16 ]. The recent work by Dorrough and Glöckner [ 17 ], measuring cooperativeness in continuous Prisoner’s Dilemma games across 12 different countries worldwide, has demonstrated that, although men generally tended to be more cooperative than women, results differed considerably between countries. Another important step which may bring us closer to understanding the mechanisms underlying same-sex cooperative behavior would be extension of the research area towards societies with different traditional socio-economic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known [ 12 – 15 ] that there are substantial cultural differences in cooperation, making it important to conduct experiments with non-WEIRD participants (WEIRD: Western, educated, industrialized, rich and democratic [ 16 ]). The recent study by Dorrough and Glöckner [ 17 ], used a continuous version of the Prisoner’s Dilemma game (actually a two-person Public Goods Game) to investigate sex differences in cooperation in a diverse set of countries (Chile, Venezuela, Mexico, USA, England, Germany, Austria, Israel, Russia, India, Australia, and Japan). Overall, men tended to cooperate more than women, but there were substantial differences across countries: almost no sex differences were observed in Germany, USA, and Venezuela; sex differences were very pronounced in Japan, with men being more cooperative; and, in contrast to all other countries, women tended to be more cooperative than men in Russia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in dictator games, in which the player assigned to be a “dictator” can decide whether they wish to selflessly share their experimental endowment with a passive player, women often transfer more money to the interaction partner than men do (e.g., Eckel & Grossman, 1998; Engel, 2011). However, in economic games (e.g., trust games, Romano, Balliet, Yamagishi, & Liu, 2017; prisoner's dilemma games, Dorrough & Glöckner, 2019) that involve the risk of exploitation (where the player transfers money and the interaction partner does not), men typically transfer more money to interaction partners than women do (for an overview regarding the different motives in economic games, see Thielmann, Böhm, & Hilbig, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, gender differences in preferences (e.g., social and risk preferences; Falk & Hermle, 2018) and basic values (e.g., power, hedonism; Schwartz & Rubel‐Lifschitz, 2009) were more pronounced in countries that ranked high (rather than low) on gender equality. Moreover, research has shown variation in the size of gender differences in prosocial behavior (in a prisoner's dilemma game) across different countries, without finding a systematic relationship between gender differences and gender equality (as measured by the Gender Inequality Index [GII]; http://hdr.undp.org/en/content/gender-inequality-index-gii; Dorrough & Glöckner, 2019). Thus, it seems especially important to shed light on the question of whether or not gender segregation in the occupational domain influences gender differences in prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%